2021
DOI: 10.1186/s13287-021-02233-9
|View full text |Cite
|
Sign up to set email alerts
|

Robust expansion and functional maturation of human hepatoblasts by chemical strategy

Abstract: Background Chemically strategies to generate hepatic cells from human pluripotent stem cells (hPSCs) for the potential clinical application have been improved. However, producing high quality and large quantities of hepatic cells remain challenging, especially in terms of step-wise efficacy and cost-effective production requires more improvements. Methods Here, we systematically evaluated chemical compounds for hepatoblast (HB) expansion and matura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Our recent study has identi ed that Vc, FSK, and Dihexa could replace BMP4, EGF, and HGF, respectively, supporting HBs expansion and maintenance [13]. Also, we demonstrated that Vc could phosphorylate BMP downstream Smad1/5/8, consistent with the previous report that Vc serves a similar effect in cardiomyogenesis [40].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our recent study has identi ed that Vc, FSK, and Dihexa could replace BMP4, EGF, and HGF, respectively, supporting HBs expansion and maintenance [13]. Also, we demonstrated that Vc could phosphorylate BMP downstream Smad1/5/8, consistent with the previous report that Vc serves a similar effect in cardiomyogenesis [40].…”
Section: Discussionsupporting
confidence: 91%
“…Hence expanding HBs, especially in small-molecule culture conditions to scalable expand HBs derived from hPSCs would be an ideal strategy for e cient, large-scale, and cost-effective generating hepatic cells for the potential clinical application [12,42]. According to this view, our previous study has established a robust and cost-effective small-molecule culture condition for the generation of self-renewing HBs and functional mature HLCs [13]. Thus, we then adopted the previously established culture condition to expand the small-molecule derived HBs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hiPSC-derived AT2-like cell cultures were also analyzed regarding other endodermal phenotypes. No similarities were detected between AT2-like cells and hepatocytes (Alpha-1-Fetoprotein expression 51 , 52 ), thyroid-like cells (PAX8 expression in LPCs) or proximal airway markers (see Supplementary Figs. S5 f, S6 , S13 , online).…”
Section: Resultsmentioning
confidence: 99%